2011
DOI: 10.3109/00498254.2011.615954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genistein on the activities of cytochrome P450 3A and P-glycoprotein in Chinese healthy participants

Abstract: To determine the effect of genistein on cytochrome P450 3A (CYP3A) and P-glycoprotein (P-gp) function using the probe substrates midazolam and talinolol, respectively. Eighteen healthy adult male participants were enrolled in a two-phase randomized crossover design. In each phase, the participants received placebo or genistein for 14 days. On the 15th day, midazolam and talinolol were administered and blood samples were obtained. Midazolam and talinolol pharmacokinetic parameter values were calculated and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Inhibition of detoxifying metabolic enzymes (CYP3A4) and ABC transport proteins, reducing drug efflux, can increase systemic and intracellular levels of taxanes, which increases their bioavailability, but also toxicity and side effects. Inhibition of CYP3A4 activity by genistein has been demonstrated in vitro and in clinical trials and we observed similar effects in our in vitro experiments. We also found considerable inhibition of efflux activity by genistein.…”
Section: Discussionsupporting
confidence: 90%
“…Inhibition of detoxifying metabolic enzymes (CYP3A4) and ABC transport proteins, reducing drug efflux, can increase systemic and intracellular levels of taxanes, which increases their bioavailability, but also toxicity and side effects. Inhibition of CYP3A4 activity by genistein has been demonstrated in vitro and in clinical trials and we observed similar effects in our in vitro experiments. We also found considerable inhibition of efflux activity by genistein.…”
Section: Discussionsupporting
confidence: 90%
“…36 On the other hand, there have been studies that showed contradictory results where Gen increased Pgp expression and function at 1 and 10 µM in the hepatocellular carcinoma-derived HepG2 cell line, 37 and 14 days' administration of Gen reduced oral bioavailability of talinolol, a Pgp substrate, in healthy human participants. 38 At any rate, Gen showed a modest induction of Pgp activity at 200 µM in the present study, and this should be considered in the interpretation of the results obtained using Gen. In the case of Cpz, Rho uptake was increased by 22%, suggesting modest inhibition of Pgp by Cpz.…”
Section: Discussionmentioning
confidence: 45%
“…In contrast, although genistein diets also had no effect on expression of rat hepatic CYP3A2, both dietary daidzein and phytochemical stripped soy protein diets significantly increased expression of CYP3A2 mRNA, CYP3A2 protein and testosterone 6β-hydroxylase activity (Ronis et al 2006b). A recent clinical study in healthy Chinese volunteers receiving genistein for 14 days reported significant increases in clearance of CYP3A substrates midazolam and talinolol suggesting that consumption of genistein supplements may result in a modest increase in CYP3A in humans (Xiao et al 2012). …”
Section: Isoflavones Pxr-signaling and Cyp3a Enzymesmentioning
confidence: 99%